The Overview of Self-Medication Knowledge Levels use of Dysmenorhore Drugs in Class 12 Students 2 Bukittinggi City - Mulyani, Dwi; Fadila Sandytia; Hilmarni (Jurnal Kesehatan Cendikia Jenius, 2024)
Dysmenorrhea, or menstrual cramps, is a common condition experienced by women during menstruation. Primary dysmenorrhea is a mild condition that can be treated through self-medication, which refers to individuals treating themselves with medications considered safe, including modern, herbal, or traditional remedies. However, improper self-medication may lead to medication errors. This study aims to assess the level of knowledge among the female students of MAN 2 Bukittinggi regarding self-medication for dysmenorrhea. This descriptive observational study used a questionnaire in the form of a Google Form to measure knowledge about dysmenorrhea and pain-relieving medications. The sample consisted of 67 students selected through purposive sampling. The results showed that the majority of respondents (97%) had good knowledge, while 1.5% had adequate knowledge, and 1.5% had poor knowledge. Based on these findings, it can be concluded that most students (97%) engage in self-medication for dysmenorrhea with a good level of knowledge. The study recommends that future research explore the relationship between knowledge and self-medication behavior, and suggests further socialization efforts by schools and healthcare providers to improve students' ability to self-medicate dysmenorrhea more effectively.